Continuum descriptions of spatial spreading for heterogeneous cell populations: Theory and experiment. (7th December 2019) - Matsiaka, Oleksii M.; Baker, Ruth E.; Simpson, Matthew J.
Highlights: New continuum model of cell migration explicitly accounts for heterogeneous cell populations. Heterogeneous model parameterised with experimental data incorporating heterogeneity in cell sizes. Compare performance of heterogeneous model and simpler homogeneous model for a range of types of heterogeneity. For some forms of heterogeneity, it is reasonable to use a simpler homogeneous model. Exploration of heterogeneity extended to deal with heterogeneity in parameters governing both undirected and directed cell motility. Abstract: Variability in cell populations is frequently observed in both in vitro and in vivo settings. Intrinsic differences within populations of cells, such as differences in cell sizes or differences in rates of cell motility, can be present even within a population of cells from the same cell line. We refer to this variability as cell heterogeneity . Mathematical models of cell migration, for example, in the context of tumour growth and metastatic invasion, often account for both undirected (random) migration and directed migration that is mediated by cell-to-cell contacts and cell-to-cell adhesion. A key feature of standard models is that they often assume that the population is composed of identical cells with constant properties. This leads to relatively simple single-species homogeneous models that neglect the role of heterogeneity. In this work, we use a continuum modelling approach to explore the role of heterogeneity in spatial spreading of cell populations. We employ a three-species heterogeneous model of cell motility that explicitly incorporates different types of experimentally-motivated heterogeneity in cell sizes: (i) monotonically decreasing; (ii) uniform; (iii) non-monotonic; and (iv) monotonically increasing distributions of cell size. Comparing the density profiles generated by the three-species heterogeneous model with density profiles predicted by a more standard single-species homogeneous model reveals that when we are dealing with monotonically decreasing and uniform distributions a simple and computationally efficient single-species homogeneous model can be remarkably accurate in describing the evolution of a heterogeneous cell population. In contrast, we find that the simpler single-species homogeneous model performs relatively poorly when applied to non-monotonic and monotonically increasing distributions of cell sizes. Additional results for heterogeneity in parameters describing both undirected and directed cell migration are also considered, and we find that similar results apply.